2016
DOI: 10.1002/aenm.201670039
|View full text |Cite
|
Sign up to set email alerts
|

Lithium‐Sulfur Batteries: Tuning Transition Metal Oxide–Sulfur Interactions for Long Life Lithium Sulfur Batteries: The “Goldilocks” Principle (Adv. Energy Mater. 6/2016)

Abstract: In article number 1501636, Linda Nazar and co‐workers demonstrate the nature of the interaction between metal oxides and polysulfides, with an aim to explore materials with the ability to chemically entrap polysulfides. The insight gained into the fundamental surface mechanism, and its correlation to the stability of the electrochemical cell, provides a bridge between mechanistic understanding and battery performance, which is essential for the design of high performance Li‐S cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…After the adsorption experiment, the S 2p 3/2 spectrum in Figure 3b ), bridged sulfur atom (S B 0 ), polythionate, and sulfur thiosulfate species, respectively. 45 The REDOX reaction between LiPSs and TNO produces thiosulfate (S 2 O 3 2− ), which can effectively adsorb LiPSs and inhibit the LiPS shuttle effect. 46 Moreover, the XPS spectra of Ti 2p and Nb 3d before and after adsorbing Li 2 S 6 are shown in Figure 3c,d.…”
Section: Resultsmentioning
confidence: 99%
“…After the adsorption experiment, the S 2p 3/2 spectrum in Figure 3b ), bridged sulfur atom (S B 0 ), polythionate, and sulfur thiosulfate species, respectively. 45 The REDOX reaction between LiPSs and TNO produces thiosulfate (S 2 O 3 2− ), which can effectively adsorb LiPSs and inhibit the LiPS shuttle effect. 46 Moreover, the XPS spectra of Ti 2p and Nb 3d before and after adsorbing Li 2 S 6 are shown in Figure 3c,d.…”
Section: Resultsmentioning
confidence: 99%
“…The most common additives are capable of trapping polysulfides in their cavities, an illustrative example is porous carbons, [4][5][6] or by electrostatic interaction with polar species, an illustrative example is metal oxides. [7][8][9] Metal-organic frameworks (MOF) are materials that meet both conditions, with a system of pores available to trap polysulfides and the polarity of the MÀ O bonds favours the electrostatic interaction, showing interesting conditions for energy storage systems. [10][11][12][13] This property was confirmed by the pioneering work of Tarascon et al [14] on MIL-100(Cr) MOF, although the SÀ MOF composites gave moderate performances.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, lithium–sulfur (Li–S) batteries have attracted a great deal of attention because of their high theoretical energy density (2600 Wh kg –1 ). In addition to the superior theoretical capacity of sulfur (1675 mAh g –1 ) as cathode material, elemental sulfur has several other advantages such as low cost, natural abundance, and environmental benignity. However, commercial implementation of Li–S batteries has been hindered by a series of obstacles: (1) ultralow electronic conductivities of elemental sulfur (S 8 , 5 × 10 –30 S cm –1 ) and its discharge product (Li 2 S 2 and Li 2 S) lead to slow kinetics reaction and low utilization of sulfur; (2) large volumetric expansion of sulfur upon lithiation (80%) makes the cathode structure unstable and thereby deteriorates the cycle performance; (3) the lithium polysulfide intermediates (Li 2 S x , 4 ≤ x ≤ 8) can dissolve into the organic electrolyte and migrate to the anode side. This undesired “shuttle effect” results in fast capacity decay and low Coulombic efficiency. Suppression of the polysulfide shuttle upon cycling is still the main challenge to realize the practical applications of Li–S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that polar metal oxides can capture the soluble polysulfides by chemical adsorption and effectively reduce the sulfur loss. In particular, some of the oxides could promote the conversion of sulfur to solid Li 2 S during lithiation. , Nonetheless, the shuttle effect still occurs at high loading of sulfur because the capture of lithium polysulfides is limited by the interface of polysulfides and oxides. In addition, the poor conductivities of oxide hosts are not beneficial to electron transport and conversion reaction of sulfur.…”
Section: Introductionmentioning
confidence: 99%